Complexes of Ni(II), Cu(II), Zn(II), Pd(II) and Cd(II) with 1-Salicylidene-4-Pyrrolidino Thiosemicarbazone - Saxena, M.K.; Singh, Rajeshwar; Sinha, B.K.; Srivastava, J.P. (Asian Journal of Chemistry, 2010)
Complexes of Ni(II), Cu(II), Zn(II), Pd(II) and Cd(II) with 1-salicylidene-4-pyrrolidino thiosemicarbazone (H2-sptsc) of general formulae [M(H-sptsc)2], M(sptsc). nH2O and [M(sptsc)py] (M = Ni2+, Cu2+, Zn2+, Pd2+, or Cd2+; n = 0 or 1) have been prepared and characterised by elemental analyses, molar conductance, magnetic susceptibility, infrared and electronic spectral measurements.